P88 The potential impact of hematocrit correction on evaluation of tacrolimus target exposure in pediatric kidney transplant patients. Issue 6 (17th May 2019) - Schijvens, A; van Hesteren, F; Cornelissen, M; Bootsma-Robroeks, C; Brüggemann, R; Burger, D; de Wildt, S; Schreuder, M; ter Heine, R
Abstract : Background: Tacrolimus is an important immunosuppressive agent with high intra- and interindividual pharmacokinetic variability and a narrow therapeutic index. As tacrolimus extensively accumulates in erythrocytes, hematocrit is a key factor in the interpretation of tacrolimus whole blood concentrations. However, as hematocrit values in pediatric kidney transplant patients are highly variable after kidney transplantation, translating whole blood concentration targets without taking hematocrit into consideration, is theoretically incorrect. The aim of this study is to evaluate the potential impact of hematocrit correction on tacrolimus target exposure in pediatric kidney transplant patients. Methods: Data were obtained from 36 pediatric kidney transplant patients. 255 tacrolimus whole blood samples were available, together responsible for 36 area under the concentration time curves (AUCs) and trough concentrations. First, hematocrit-corrected concentrations were derived using a formula describing the relationship between whole blood concentrations, hematocrit, and plasma concentrations. Subsequently, target exposure was evaluated using the converted plasma target concentrations. Ultimately, differences in interpretation of target exposure were identified and evaluated. Results: In total, 92% of our patients had a lower hematocrit (median 0.29) than the reference value of adult renal transplant patients. A different evaluation of target exposure for either trough level, AUC or both, was defined in 42% of our patients, when applying hematocrit corrected concentrations. Conclusion: A critical role for hematocrit in therapeutic drug monitoring of tacrolimus in pediatric kidney transplant patients is suggested in this study. Therefore, we believe that hematocrit correction could be a step towards improvement of tacrolimus dose individualization. Disclosure(s): All authors declare that they have no conflict of interest. This work was recently accepted for publication in Pediatric Nephrology. We are aware of the statement in the guideline about previously published work, however as we believe that this work suits the aim and topics of the congress very well, we chose to submit this work and will ofcourse leave the final decision to you.